Grain boundaries in CdTe thin film solar cells: a review. (21st July 2016) - Major, Jonathan D
Abstract: The current state of knowledge on the impact of grain boundaries in CdTe solar cells is reviewed with emphasis being placed on working cell structures. The role of the chemical composition of grain boundaries as well as growth processes are discussed, along with characterisation techniques such as electron beam induced current and cathodoluminescence, which are capable of extracting information on a level of resolution comparable to the size of the grain boundaries. Work which attempts to relate grain boundaries to device efficiency is also assessed and gaps in the current knowledge are highlighted.